Інноваційне освітнє середовище у закладах вищої освіти – педагогічна умова формування професійної компетентності майбутніх бакалаврів хіміко-технологічної підготовки - Курбанова, Халіда (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті обґрунтовано думку щодо створення інноваційного освітнього середовища у закладах вищої освіти як однієї з педагогічних умов формування професійної компетентності майбутніх бакалаврів хіміко-технологічної підготовки; розкрито погляди науковців на підготовку фахівців нової якості; наведено визначення таких понять, як "інноваційна освіта", "педагогічні інновації"; наведено технологічну складову формування інноваційного освітнього середовища у ЗВО, основні завдання наукової та інноваційної діяльності університету; розглянуто застосування інноваційних технологій в освітньому процесі та форми і методи їх реалізації; запропоновано застосування сучасних технологій ("кейс-технологій", М-Learning – технологій, TVтехнологій, Інтернет – технологій) і впровадження методик навчання у професійній підготовці та підвищенні професійної компетентності майбутніх бакалаврів хімікотехнологічної підготовки, які сприяють засвоєнню знань, розвитку навичок та формуванню професійної компетентності (спеціальних програмних засобів, веб-серверів та інноваційних методів навчання (електронне навчання, застосування інтернетресурсів, проблемне навчання, кейс-метод, інтерактивні презентації, майндмепінг); доведено дієвість наведеної педагогічної умови.

The article substantiates the opinion regarding the creation of an innovative educational environment in institutions of higher education as one of the pedagogical conditions for the formation of professional competence of future bachelors of chemical and technological training; the views of scientists on the training of specialists of new quality are revealed; definitions of such concepts as "innovative education", "pedagogical innovations" are given; the technological component of the formation of an innovative educational environment at the ZVO, the main tasks of the scientific and innovative activity of the university are given; the application of innovative technologies in the educational process and the forms and methods of their implementation are considered; the application of modern technologies ("case technologies", M-Learning - technologies, TV- technologies, Internet - technologies) and the introduction of training methods in professional training and increasing the professional competence of future bachelors of chemical and technological training, which contribute to the assimilation of knowledge, are proposed, development of skills and formation of professional competence (special software tools, web servers and innovative teaching methods (e-learning, use of Internet resources, problem-based learning, case method, interactive presentations, mind mapping); the effectiveness of the given pedagogical conditions has been proven.
Creation of an innovative educational environment in institutions of higher education - a pedagogical condition for the formation of the professional competence of future bachelors of chemical and technological training
Keywords: освітні середовища; вища освіта; професійна компетентність; майбутні бакалаври; хіміко-технологічна підготовка; educational environment; innovations; professional competence; chemical and technological training